2019
DOI: 10.1093/femsec/fiz069
|View full text |Cite
|
Sign up to set email alerts
|

The ability of a host plant to associate with different symbiotic partners affects ectomycorrhizal functioning

Abstract: Some plants that associate with ectomycorrhizal (ECM) fungi are also able to simultaneously establish symbiosis with other types of partners. The presence of alternative partners that may provide similar benefits may affect ECM functioning. Here we compared potential leucineaminopeptidase (LA) and acid phosphatase (AP) enzyme activity (involved in N and P cycling, respectively) in ECM fungi of three hosts planted under the same conditions but differing in the type of partners: Pinus (ECM fungi only), Eucalyptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Interactions between mycorrhizal fungi and their plant hosts shape below-and aboveground communities, but few studies have addressed the outcomes of ECM and AM fungi associated with the same plant host (Queralt et al, 2019;Tedersoo and Bahram, 2019;Teste et al, 2019). Likewise, the costs and benefits of associations with either ECM or AM fungi across environmental gradients remains largely unknown in the context of forest restoration (Phillips et al, 2013;Williams et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interactions between mycorrhizal fungi and their plant hosts shape below-and aboveground communities, but few studies have addressed the outcomes of ECM and AM fungi associated with the same plant host (Queralt et al, 2019;Tedersoo and Bahram, 2019;Teste et al, 2019). Likewise, the costs and benefits of associations with either ECM or AM fungi across environmental gradients remains largely unknown in the context of forest restoration (Phillips et al, 2013;Williams et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, soil available P was highest in the native site, in correlation with a higher ECM fungal richness (Tables 1, 2). Few studies have investigated the role of ECM fungi for P uptake (Köhler et al, 2018;Queralt et al, 2019), but evidence showed that ECM-dominated stands can have easier access to organic P than AM-dominated forests (Albornoz et al, 2016;Rosling et al, 2016). Moreover, plants that form both AM and ECM associations can allocate C preferably to the fungal symbiont that provides more benefits relative to the abundance of readily available nutrients (Albornoz et al, 2016).…”
Section: The Effect Of Disturbance On Mycorrhizal Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have shown the effects of interactions between truffle plants (forming ectomycorrhizas, ECM) and shrubs and herbs (companion plants, mostly forming arbuscular mycorrhizas, AM) either cultivated or growing spontaneously in truffle brûlés [ 18 , 19 ]. Previous studies on AM–ECM fungal interactions were mostly conducted at the scale of plant individuals hosting multiple types of mycorrhizal fungi [ 20 , 21 ]. Among them, plants of the genus Quercus are confirmed to form both kinds of mycorrhizal symbioses, forming AM and ECM structures [ 22 ].…”
Section: Introductionmentioning
confidence: 99%